The Effect of Performance Appraisal, Reward, and Punishment on Machining Employee Performance at PT. Musashi Auto Parts Indonesia - Slamet Prastiyanto; Sulartopo Sulartopo (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explore the effects of Performance Appraisal systems, rewards, and punishment on the efficiency of employees working at PT. Musashi Autoparts Indonesia. This study was conducted in order to address the lack of a holistic evaluation system, equitable rewards, and justifiable punishment within the organization to enhance productivity and performance standards. This study employs associative quantitative research, which contains descriptive and verification techniques. The study’s respondents were all 43 employees, and these were collected using saturated sampling. The data was collected using a questionnaire which was analyzed based on the Likert scale. The data was analyzed using the most recent version of SPSS, and processed through validity and reliability tests, multiple linear regression, T and F tests. The research results show that each of the variables which in this case are Performance Appraisal, reward and punishment, all have a significant effect on employee performance. Of all the variables, it is rewards that have the most significant effect on performance. In light of these results, the study suggests that the company is to enhance the RP system by recognizing and rewarding top performers as well as refining the performance appraisal system to make it more objective and transparent, and set a constructive, measurable punishment system which should help to bolster employee motivation.